2006
DOI: 10.1109/iecon.2006.347229
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Perceptron Adaptive Dynamic Control for Trajectory Tracking of Mobile Robots

Abstract: This paper presents a novel functional-adaptive dynamic controller for trajectory tracking of nonholonomic wheeled mobile robots. The controller is developed in discrete-time and employs a multilayer perceptron neural network for the estimation of the robot's nonlinear dynamic functions, which are assumed to be completely unknown. On-line weight tuning is achieved by employing the extended Kalman filter algorithm, based on a specifically formulated stochastic inverse dynamic identification model of the mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…2) Sigmoidal MLP Dual Adaptive Scheme: Another type of neural network, commonly employed in control applications, is the sigmoidal MLP ANN [7], [14], [16], [45]. Unfortunately, MLP networks do not preserve the desirable property of linearity in the unknown network parameters exhibited by radial basis function networks.…”
Section: Remark 33mentioning
confidence: 99%
See 2 more Smart Citations
“…2) Sigmoidal MLP Dual Adaptive Scheme: Another type of neural network, commonly employed in control applications, is the sigmoidal MLP ANN [7], [14], [16], [45]. Unfortunately, MLP networks do not preserve the desirable property of linearity in the unknown network parameters exhibited by radial basis function networks.…”
Section: Remark 33mentioning
confidence: 99%
“…Parametric adaptive control and robust sliding mode control, have also been proposed to mitigate the problem of unknown or uncertain mobile robot parameters [8], [10]. Another approach is that of online functional-adaptive control, where the uncertainty is not restricted to parametric terms, but covers the dynamic functions themselves [7], [11], [14] [17]. We consider this approach to be more general and superior in handling higher degrees of uncertainty and unmodelled dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 3.6: ∇ h k denotes the Jacobian matrix of h (x k−1 , τ k−1 , z * k ) with respect to z * k evaluated atẑ k . By (9), (10) and (12) it can be shown that:…”
Section: Assumption 32mentioning
confidence: 99%
“…[9][10][11][12][13] Houshangi and Azizi 7 integrated the information from odometry and gyroscope using UKF. To improve the performance of odometry, a fiber optic gyroscope is used to give the orientation information that is more reliable.…”
mentioning
confidence: 99%